Design Solution for Equipment Layout and Interfaces of Car Washing Tracks at Fully Automatic Operation Depots in Urban Rail Transit Systems - LI Yong (Kongzhi Yu Xinxi Jishu)
With the development of fully automatic operation technologies, the GoA4-level fully automatic operation system has emerged as the preferred choice for constructing new urban rail transit lines. In these systems, fully automatic car washing is deemed an important functional component. This paper presents a solution for this function that fully aligns with the design requirements for fully automatic operation systems. This solution addresses the layout of signal equipment for car washing tracks in different configurations and includes the design of interfaces between the signal system and car washer control system, as well as information transmission and circuit at these interfaces taking into account specific requirements for car washing operations. Additionally, it incorporates additional safety protection measures, such as safety protection distances and fail-safe principles. Furthermore, the car washing operation processes are detailed for different track configurations and different washing modes, along with procedures related to the signal system for handling abnormal states during the car washing operation process. Through simulations and experiments, the proposed solution was verified to be safe and reliable in implementing the automatic car washing function on car washing tracks in different configurations, providing a reference for designing equipment layouts and interfaces on these tracks in fully automatic operation systems.